History and art in neurology [Nörolojideki tarih ve san'at] - (:unkn) unknown (My University, 2007)
Most of the medical verbs and eponyms which we use today have been derived from mythology and history. People were interested in medicine and treating diseases even in ancient times. Many medical verbs have been originated from dedication to the person who was related with the disease mostly by giving his name to the illness. Giving the name of the famous sufferer to the illness has been another common approach. Literal characters as well as mythological ones and sometimes the figures of a painter may inspire for a medical verb. It's obvious that being a perfect clinician doesn't require the knowledge of epilepsy's or oromandibular distony's historical names. However; remembering these original terms including the ones which are not in use today civilizes neurology and join the two major parts of medicine; science and art. Even though current tendency among clinicians is to neglect art, these two major parts complete each other. It's not possible to mention all the stories in an article since this will probably account for a thick book. Popular and entertaining ones have been presented to the readers here.
Keywords: Art; History; Mythology; Neurology